2021
DOI: 10.1371/journal.pntd.0009294
|View full text |Cite
|
Sign up to set email alerts
|

An open label, randomized clinical trial to compare the tolerability and efficacy of ivermectin plus diethylcarbamazine and albendazole vs. diethylcarbamazine plus albendazole for treatment of brugian filariasis in Indonesia

Abstract: Improved treatments for lymphatic filariasis (LF) could accelerate the global elimination program for this disease. A triple drug combination of the anti-filarial drugs ivermectin, diethylcarbamazine (DEC) and albendazole (IDA) has been shown to be safe and effective for achieving sustained clearance of microfilariae (Mf) of the filarial parasite Wuchereria bancrofti from human blood. However, the triple drug combination has not been previously been evaluated for treatment of brugian filariasis, which accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In conclusion, community MDA with IDA was safe, well tolerated and significantly more effective than the reference MDA regimen (DA) for clearing Mf. These results are consistent with observations of superior Mf clearance with IDA in similar studies in Haiti, India and Indonesia [ 28 , 30 , 31 ], noting that IDA was observed to have comparable efficacy to DA in a similar study in Fiji [ 32 ]. The new regimen has the potential to fast-track LF elimination in PNG and in many other endemic areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, community MDA with IDA was safe, well tolerated and significantly more effective than the reference MDA regimen (DA) for clearing Mf. These results are consistent with observations of superior Mf clearance with IDA in similar studies in Haiti, India and Indonesia [ 28 , 30 , 31 ], noting that IDA was observed to have comparable efficacy to DA in a similar study in Fiji [ 32 ]. The new regimen has the potential to fast-track LF elimination in PNG and in many other endemic areas.…”
Section: Discussionsupporting
confidence: 91%
“…This is likely due to the more rapid clearance of Mf after drug treatment with IDA because of the additional microfilaricidal activity of ivermectin giving rise to increased filarial DNA and circulating filarial antigens activating inflammatory responses and elevated cytokine levels [19]. The higher rate of AEs in adults is likely due to their higher infection prevalence relative to children and was similarly observed in the other trial sites of India, Indonesia, Haiti and Fiji [28][29][30][31].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An overview of the various uses and dosimetry is listed in Table 1 . [ 1 41 42 43 51 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 ]…”
Section: Indications In Dermatology and Tropical Medicinementioning
confidence: 99%
“…A recent trial showed that triple-drug treatment with an oral dose of IVM (200 μg/kg body weight), DEC (6 mg/kg), and albendazole (a fixed dose of 400 mg) was better than DEC and albendazole and this would seem to be a better option for brugian filariasis. [ 60 61 ]…”
Section: Indications In Dermatology and Tropical Medicinementioning
confidence: 99%